Bulk RNA degradation by nitrogen starvation‐induced autophagy in yeast. (2nd December 2014) - Huang, Hanghang; Kawamata, Tomoko; Horie, Tetsuro; Tsugawa, Hiroshi; Nakayama, Yasumune; Ohsumi, Yoshinori; Fukusaki, Eiichiro
Abstract Autophagy is a catabolic process conserved among eukaryotes. Under nutrient starvation, a portion of the cytoplasm is non‐selectively sequestered into autophagosomes. Consequently, ribosomes are delivered to the vacuole/lysosome for destruction, but the precise mechanism of autophagic RNA degradation and its physiological implications for cellular metabolism remain unknown. We characterized autophagy‐dependent RNA catabolism using a combination of metabolome and molecular biological analyses in yeast. RNA delivered to the vacuole was processed by Rny1, a T2‐type ribonuclease, generating 3′‐NMPs that were immediately converted to nucleosides by the vacuolar non‐specific phosphatase Pho8. In the cytoplasm, these nucleosides were broken down by the nucleosidases Pnp1 and Urh1. Most of the resultant bases were not re‐assimilated, but excreted from the cell. Bulk non‐selective autophagy causes drastic perturbation of metabolism, which must be minimized to maintain intracellular homeostasis.